ONLINE QUEUING SYSTEM BAP PASSPORT INDONESIAN CITIZEN AT CLASS I NON-TPI IMMIGRATION OFFICE BEKASI - W Wilonotomo; Priati Assiroj; Reno Mareno Sidik (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The conventional method used for queuing services for Indonesian passport BAP is no longer relevant to these circumstances and the covid-19 pandemic and has not been able to answer future immigration challenges. The current queuing system is that applicants must come to the immigration office for scheduling processing and then be recorded by manual book officer queue. The Online Queue System for Indonesian Passport BAP can be a solution to help current problems and answer future challenges. The online queuing system that will be implemented can be processed through a queuing system link that can be posted on the social media of the Bekasi immigration office. The online queuing system cycle method used by the author in this online queuing system is a waterfall method where each stage must be completed before entering the next phase. Starting from analyzing system requirements, system design, system implementation, system testing, and system implementation and maintenance. The result of the process is that the online queuing system for Indonesian passport BAP has gone through each stage well so that the online queuing system is feasible to implement. The online queuing system is expected to help the intelligence section and prosecution of the Bekasi immigration office provide convenience for applicants and is very effective with the ongoing COVID-19 pandemic conditions and responds to future service challenges.